Pengembangan Perangkat Pembelajaran Etno-digital dengan Materi Prisma untuk Meningkatkan Hasil Belajar Siswa - Rochmadyan, Nabillah Ayuditya; Zayyadi, Moh. (Universitas Islam Jember, 2025)
Mathematics is often considered difficult because the material taught is not closely connected to students’ daily-life. Ethnomathematics offers an alternative approach by linking mathematical concept with local culture. Meanwhile, digital technology enables content delivery more interactively and engagingly. This research aims to develop an ethno-digital learning toll that is valid, practical, and effective ini improving student learning outcomes at SMP Negeri 1 Pamekasan. This research uses the Research and Development (R&D) method with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The developed device integrates local cultural elements with digital media to create contextual and meaningful learning. The research instruments include validation sheets, teacher and student response questionnaires, and learning outcome tests. The validation results indicated that the device is highly valid and user-friendly, and it received positive feedback. The significant improvement in student learning outcomes in the experimental class shows that the device is suitable for use in the mathematics education. Keywords: learning devices, ethno-digital, prism, learning outcomes, mathematics